Musical Improvisation for Promoting Parent-Child Interaction - Monica Subiantoro (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2017)
This study aims to examine parents' experiences on improvisation and investigate how it contributes to the development of parent-child interaction in a music therapy group. Using qualitative method, it involves a questionnaire, semi-structured interview and observation on musical behavior through video analysis. The result shows that although parents initially feel hesitant to respond to this new activity, parents and children benefit from having improvised music in the session. The benefits include increasing spontaneity, self-expression without language barriers, allowing parents to interact with their child and for their child to interact with other children. Community also supports its members to bring out their improvising selves.